PENGETAHUAN DAN SIKAP REMAJA TERHADAP NARKOBA DAN HIV/AIDS DI DISTRIK MUARA TAMI JAYAPURA - Oktliana Pasangka; Elisabet Bre Boli; Dwi Astuti (Universitas Fort De Kock, 2023)
Adolescent’s hight curiosity can lead into negative impact on the growth of adolescents, such as drug abuse and free sex which can be at risk of contracting diseases such as the Human Immunodeficiency Virus (HIV). Drug users in Jayapura are mostly 12-18 years old, of the total drug users being treated at BNN Papua, and HIV/AIDS cases in Papua in 2022, about 50.011 cases.. The aim of this study is to determine the relationship between knowledge and attitudes of adolescents towards drugs and HIV/AIDS in Muara Tami Jayapura District. Quantitative research with a cross sectional design was conductedwith the number of sample is 212 respondents who live in the Holtekamp area, Muara Tami District. Data was collected through interviews with a questionnaire. Chi-Square test found that there was a relationship between the level of education and the level of knowledge of adolescents about HIV/AIDS (p-value 0.006). There is also a relationship between the level of knowledge and attitudes of adolescents towards drugs (p-value 0.000). The better the level of knowledge of adolescents about drugs, the better attitudes in dealing with drugs. It is necessary to increase the knowledge of adolescents related to drugs to prevent drug abuse